Phenylethanoid glycosides from traditional Mongolian medicine Cymbaria daurica alleviate alloxan-induced INS-1 cells oxidative stress and apoptosis - Ruyu Shi; Xing Li; Bing Gao; Chunhong Zhang; Minhui Li (Food Science and Human Wellness)
Cymbaria daurica L. is a well-known traditional Mongolian medicine, which has been used to treat diabetes-related conditions characterized by persistent thirst and hunger, copious urination, and weight loss. We aimed to investigate the protective effects of C. daurica extracts and phenylethanoid glycosides including verbascoside and isoacteoside on INS-1 cells. We discovered phenylethanoid glycosides from n-butanol extract with large content through extraction and separation. We continue to study the protective effects of phenylethanoid glycosides including verbascoside and isoacteoside on INS-1 cells. INS-1 cells were treated with C. daurica, cell viability assay, RNA-seq technology, superoxide dismutase activity and malonaldehyde content, quantitative real time-PCR and Western blot analysis were used to study the protective effects of C. daurica. Cell viability assay resulted that n-butanol extract and verbascoside, isoacteoside showed protective effects of C. daurica. According to the RNA-seq technology to identify the differentially expressed genes in INS-1 cells, the pathway of gene enrich the protective effect of C. daurica on oxidative stress. SOD activity and the content of MDA indicated that C. daurica could enhance the antioxidant capacity of INS-1 cells. Further investigation indicated C. daurica alleviate oxidative stress by inhibiting INS-1 cell apoptosis. C. daurica may play an anti-diabetic role by inhibiting islet cell apoptosis.